2020
DOI: 10.1172/jci.insight.134520
|View full text |Cite
|
Sign up to set email alerts
|

Monounsaturated fat rapidly induces hepatic gluconeogenesis and whole-body insulin resistance

Abstract: BACKGROUND.While saturated fat intake leads to insulin resistance and nonalcoholic fatty liver, Mediterranean-like diets enriched in monounsaturated fatty acids (MUFA) may have beneficial effects. This study examined effects of MUFA on tissue-specific insulin sensitivity and energy metabolism. METHODS.A randomized placebo-controlled cross-over study enrolled 16 glucose-tolerant volunteers to receive either oil (OIL, ~1.18 g/kg), rich in MUFA, or vehicle (VCL, water) on 2 occasions. Insulin sensitivity was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 40 publications
3
27
1
1
Order By: Relevance
“…Serum or plasma FGF21 levels were measured using the Quantikine ELISA Human FGF21 kit (R&D Systems, Minneapolis, coefficient of variation: Intra-Assay, 3.4%, Interassay 7.5%) according to the manufacturer's instructions. Our control values were similar to prior studies conducted in either serum or plasma with this kit, and its accuracy has been validated in both [45][46][47][48][49][50] . Samples were run in duplicate.…”
Section: Blood Fgf21 Measurementssupporting
confidence: 82%
“…Serum or plasma FGF21 levels were measured using the Quantikine ELISA Human FGF21 kit (R&D Systems, Minneapolis, coefficient of variation: Intra-Assay, 3.4%, Interassay 7.5%) according to the manufacturer's instructions. Our control values were similar to prior studies conducted in either serum or plasma with this kit, and its accuracy has been validated in both [45][46][47][48][49][50] . Samples were run in duplicate.…”
Section: Blood Fgf21 Measurementssupporting
confidence: 82%
“…Moreover, the results of this short-term study in healthy humans cannot be necessarily extrapolated to chronic lipid oversupply or common insulin resistance of obesity and type 2 diabetes. Nevertheless, our approach represents an accepted compromise between optimal experimental and near-physiological conditions to allow for assessing acute metabolic changes [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma FA analysis NEFA were analysed as their FA methyl esters (FAMEs) using GC-MS, as described in detail elsewhere [10,14]. Direct transesterification of all classes of lipids was carried out in a one-step reaction [14].…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic glycogen synthesis and degradation fluxes are key components of systemic glucose homeostasis and are highly sensitive to the insulin/glucagon ratio. The application of in vivo 13 C MR to measure changes in hepatic glycogen during fasting and feeding has advanced our understanding of hepatic carbohydrate metabolism in subjects with insulin resistance, as well as in patients with diabetes [65][66][67][68][69]. Among other things, it revealed that while both hepatic glycogen deposition and degradation rates are significantly reduced in Type-1 diabetic subjects undergoing standard insulin therapy, these fluxes may be restored to normal with intensive insulin therapy [70,71].…”
Section: [56]mentioning
confidence: 99%